Social Relationship Patterns in Multicultural Society and The Role of Media - P, Ravi Kumar; Varghese, PA (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Religion is playing a crucial role in multicultural country like India. The social relationship patterns among respondents heavily depend upon their religion and cultural traditions. Here the social convergence and communal harmony is very important in development of the nation. The role of media is also important in multicultural society to bring all the people under one roof. So, here researcher identifies the responsibility of media in presenting the content in the form of creating towards a secular society. How to cite this article: Kumar RP, Varghese PA. Social Relationship Patterns in Multicultural Society and The Role of Media. J Adv Res Jour Mass Comm 2018; 5(1&2): 34-38. DOI: https://doi.org/10.24321/2395.3810.201806